1996
DOI: 10.1152/ajpheart.1996.271.2.h696
|View full text |Cite
|
Sign up to set email alerts
|

Inward rectifier K+ currents in smooth muscle cells from rat coronary arteries: block by Mg2+, Ca2+, and Ba2+

Abstract: Inward rectifier K+ channels have been implicated in the control of membrane potential and external K(+)-induced dilations of small coronary arteries. To identify and characterize inward rectifier K+ currents in coronary artery smooth muscle, whole cell K+ currents in smooth muscle cells enzymatically isolated from rat coronary (septal) arteries (diameters, 100-150 microns) were measured in the conventional and perforated configurations of the patch-clamp technique. Ba(2+)-sensitive, whole cell K+ current-volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
104
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(131 citation statements)
references
References 0 publications
25
104
2
Order By: Relevance
“…However, at least one mechanism would be a plausible reason. As high K + induced an increase in K ir conductance (Jiang et al, 2001;Robertson et al, 1996), which was indicated by an initial transient large hyperpolarization followed by a small sustained hyperpolarization in high V m cells (Fig. 7C, also (Jiang et al, 2001), the increased K ir conductance should exert a shunting effect on the ACh-induced current, causing a reduction of the depolarization.…”
Section: The Activation Of a Cation Conductancementioning
confidence: 93%
“…However, at least one mechanism would be a plausible reason. As high K + induced an increase in K ir conductance (Jiang et al, 2001;Robertson et al, 1996), which was indicated by an initial transient large hyperpolarization followed by a small sustained hyperpolarization in high V m cells (Fig. 7C, also (Jiang et al, 2001), the increased K ir conductance should exert a shunting effect on the ACh-induced current, causing a reduction of the depolarization.…”
Section: The Activation Of a Cation Conductancementioning
confidence: 93%
“…The endothelium was removed on a portion of the artery samples by inverting the artery and scraping the lumenal surface with a glass slide. Vascular smooth muscle cells were isolated by a procedure previously described (Robertson et al 1996). Briefly, intact arteries were placed into the above-mentioned extracellular solution which included 1 mg ml¢ papain, 1 mg ml¢ bovine serum albumin (BSA), and 1 mg ml¢ dithioerythritol, and incubated for various time periods (20 min for coronary arteries; 30 min for basilar arteries; 35 min for mesenteric arteries) at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that strong, inwardly rectifying K¤ currents in native vascular smooth muscle cells are sensitive to extracellular K¤ and low (ìÒ) concentrations of Ba¥ (Quayle et al 1993;Robertson et al 1996). It has previously been shown that a change in external K¤ had a number of effects on Kir currents: (1) rectification shifted with EK; (2) Erev for the current was a function of the EK; and (3) inward conductance increased with external K¤ concentration.…”
Section: Xenopus Oocytesmentioning
confidence: 99%
“…Regardless of their origin within the cardiovascular system, K IR currents recorded to date are potently blocked by micromolar external Ba 2+ ions in a manner that is steeply voltage and time-dependent (Quayle et al, 1993;Robertson et al, 1996;Bradley et al, 1999;Snetkov & Ward, 1999;Sakai et al, 2002;Oonuma et al, 2002).…”
Section: Introductionmentioning
confidence: 99%